Abnormal spiral artery remodelling in the decidual segment during pregnancy: from histology to clinical correlation. Issue 12 (11th August 2011) - Avagliano, Laura; Bulfamante, Gaetano Pietro; Morabito, Alberto; Marconi, Anna Maria
Abstract : Introduction: Modification of the spiral arteries with loss of the muscular vascular wall, invaded by the trophoblasts, represents the goal of the physiological vascular adaptation during human implantation. When physiological vascular changes do not occur, an unfavourable evolution of gestation may develop as suggested by uterine biopsies studies. Aims: To evaluate the prevalence of the abnormal spiral arteries modification (ASAM) through the routine examination of placentas, to identify maternal predisposing factors and to examine the correlations between the histological lesion and pregnancy outcome. Methods: 1534 consecutive singleton pregnancies were retrospectively analysed. An extensive histological and clinical investigation was performed. Results: ASAM was present in 5.8% pregnancies. When compared with cases without ASAM, cases with ASAM exhibited a higher prevalence of pre-eclampsia (10% vs 2%), placental abruption (5.5% vs 0.3%), preterm premature rupture of membranes (7% vs 1.3%) and intrauterine fetal death (18% vs 2.2%). Multivariate analysis showed that the maternal body mass index represents the major maternal pregestational factor that can influence the prevalence of ASAM (OR=1.8, 95% CI 1.1 to 3 in cases with BMI>30 kg/m 2 ). Conclusion: The abnormal modification of the decidual segment of the spiral arteries is identifiable at the time of the conventional histopathological placental evaluation and is associated with adverse pregnancy outcome. The identification of the cause of the unfavourable evolution of pregnancy is fundamental for parents, both for counselling and for prevention; the identification of ASAM in such pregnancies might provide additional valuable information.